1975
DOI: 10.1080/00071667508416189
|View full text |Cite
|
Sign up to set email alerts
|

The hen's egg: Relationships of seven characteristics of the strain of hen to the incidence of cracks and other shell defects

Abstract: 1. Multiple regression and path-coefficient analysis show that the factors with greatest influence on the incidence of cracks and other shell defects in three random-sample tests of 47 entries of 28 strains were, in descending order, mean shell colour, mean shell thickness, mean egg production and mean egg weight, and that median age at maturity, mean body weight at 140 d and mean weight increase between 140 and 500 d had no effect.2. Breeders who wish to exercise indirect selection for low crack incidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…Similar correlations between shell colour and specific gravity have been reported by Godfrey (1949), Godfrey and Jaap (1949) and Grover et al (1980), and between shell colour and shell thickness by Godfrey (1949) and Godfrey and Jaap (1949), though Carter (1975) found a significant negative correlation between shell colour and shell thickness. The high and significant negative correlation reported by Carter (1975) between egg-shell colour and incidence of shell faults, emphasises the beneficial effect of shell colour on strength. Although did not find significant relationships between egg-shell colour and four measurements of shell strength, one of the two commercial strains used showed correlations between colour and thickness and between colour and breaking strength which were almost significant and similar to those mentioned above.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar correlations between shell colour and specific gravity have been reported by Godfrey (1949), Godfrey and Jaap (1949) and Grover et al (1980), and between shell colour and shell thickness by Godfrey (1949) and Godfrey and Jaap (1949), though Carter (1975) found a significant negative correlation between shell colour and shell thickness. The high and significant negative correlation reported by Carter (1975) between egg-shell colour and incidence of shell faults, emphasises the beneficial effect of shell colour on strength. Although did not find significant relationships between egg-shell colour and four measurements of shell strength, one of the two commercial strains used showed correlations between colour and thickness and between colour and breaking strength which were almost significant and similar to those mentioned above.…”
Section: Discussionsupporting
confidence: 85%
“…Shell thickness was not predicted more accurately with both specific gravity and shell colour as independent variables than by using specific gravity alone, confirming the results of , in which shell colour was not significantly related to non-destructive deformation and breaking strength, and contradicting those reported by Carter (1975) who found that shell colour was significantly associated with reduction of shell faults. Shell thickness was predicted most accurately when specific gravity and egg weight were used as independent variables, even though the determination coefficient did not differ very much from that obtained using specific gravity alone.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The studied traits were egg albumen weight(g), yolk and shell weights(g), egg shape index as the percentage of egg width on egg length, shell without membranes thickness (mm), albumen height (mm) with micrometer. Egg surface area (cm 2 ) was calculated as the formula of Carter (1975); Eggshell density (g/cm 2 ) was calculated by the formula of Curtis et al (1985), Yolk weight %, albumen weight%, eggshell weight %, and yolk/albumen ratio were detected.…”
Section: Methodsmentioning
confidence: 99%
“…The studied traits were egg albumen weight(g), yolk and shell weights(g), egg shape index as the percentage of egg width on egg length, shell without membranes thickness (mm), albumen height (mm) with micrometer. Egg surface area (cm 2 ) was calculated as the formula of Carter (1975); Eggshell density (g/cm 2 ) was calculated by the formula of Curtis et al (1985), Yolk weight %, albumen weight%, eggshell weight %, and yolk/albumen ratio were detected.…”
Section: Methodsmentioning
confidence: 99%